Characterization and antimicrobial analysis of chitosan composite biodegradable films with addition of lemon grass essential oil - Maa Ajmalaisyatu Illani, Mohd Nawi (2010)
The increasing demand in food safety, quality, convenience and environmental concerns associated with the handling of plastic waste has emphasized the importance in developing biodegradable and edible films from natural polymers, such as chitosan. Starch-based film is considered an economical material for antimicrobial packaging. This study aimed at the development of packaging based on chitosan-tapioca starch incorporated with lemon grass essential oil as antimicrobial agents. In this research, there are three samples were prepared. Sample A containing starch-chitosan as control film, sample B containing starch-chitosan with the addition of gelatin and sample C containing starch-chitosan based film incorporated with lemon grass essential oil. For the antimicrobial analysis, all the samples were tested on B. substilis and E. coli. Inhibition of bacterial growth was examined using two methods which are zone inhibition assay and liquid culture test. From the observations, sample C exhibited a wide clear inhibitory zone rather than samples A and B. From the liquid culture test, the sample C clearly demonstrated a better inhibition against B. substilis than E. coli. Incorporation of lemon grass essential oils also led to an improvement in several films properties in terms of morphology, chemical composition and thermal properties. The result from TGA and DSC has shown the higher thermal and melting temperature possesses by the sample C and slightly miscible and compatible with the starch-chitosan composition. The addition of lemon grass essential oil proves that the film is better to film based on starch-chitosan only. Lemon grass essential oil will actually improve the performance of the chitosan composite biodegradable film as tested in this research. As a conclusion, starch-chitosan composite biodegradable film has the potential to be use for food packaging.